A constituição da feminilidade na psicanálise winnicottiana - Gomes, Kátia Pavani da Silva (2010)
This study presents the constitution of femininity in winnicottian psychoanalysis. Which can not be observed or presented as centered in the Oedipus Complex, nor even in the absence of the penis and how to deal with it. In winnicottian psychoanalysis the femininity is understood as part of the maturational process, based in instinctual and non instinctual relationships